Sociocultural Components of Existential Space - Soghomonyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
“The man in the world” (the man’s relation to the Absolute, substantive and social being) and “the man’s world” (“I” or the man’s relation to self) are the semantic constructs, which form the unified existential inner world of the man. The historical process of development of the man’s objective being may be divided into three stages: 1) the unmediated stage of the relation of man to things, when the manufactured objects are really man-made and, as such, are organically included in the unified existential space of man; 2) the mediated stage of relations to things, when the unified world of man’s being is divided into the instrumental and existential worlds, and the instrumental world represents threatening and destructive effect to the existential one; 3) the stage of "dual mediation", when even the existence of existential space becomes problematic. The structural transformations of objective being cause modifications in the existential space. The social being as a person’s relation to another one is revealed through a system of categories: "I", "You", "It", "We", where their methodological significance is emphasized. The man’s relation to the Absolute is considered as the semantic factor, which constitutes the existential space.